Procesos identitarios, “minorías” étnicas y etnicidad: los mapuches de la República Argentina - Héctor Vázquez (Amnis)
In this paper the author considers several key concepts concerning socio-cultural anthropology such as the identity process, ethnic minorities, autonomy and self-determination. The author focuses on the Argentine Mapuches.